PENGARUH PAJAK DAERAH PADA PENDAPATAN ASLI DAERAH DI KOTA DENPASAR - Marita, Ni Made; Alit Suardana, Ketut (E-Jurnal Akuntansi; Vol 14 No 1 (2016), 2016)
The purpose of this research is to find out and get information about the influence of local tax revenue to local revenue contribution in volatility environment. This research was conducted in the Department of Revenue of Denpasar by using series data (times series) quarterly from 2009 to 2013. The data was collected through structured interviews, observation participation study documentation. The analysis technique used is the contribution analysis multiple linear regression. The results showed that local tax revenue is taxes hotels, restaurants, entertainment, advertising, and street lighting tax and sigifikansi positive effect on revenue as the dependent variable in a volatile environment.
Keywords: Hotel tax, restaurant tax, entertainment tax, advertisement tax, street lighting tax and revenue (PAD)